Antioxidant and neuroprotective effects of nutriosomes and grape pomace phytochemicals in a cell model of oxidative stress and mouse model of Parkinson disease - Mohamad Allaw; Matteo Perra; Pathik Parekh; Marcello Serra; Jacopo Marongiu; Ines Castangia; Federica Fulgheri; Pierluigi Caboni; Giulia Tolle; Francesco Corrias; Fabiano Asunis; Gabriele Giua; et al. (Scientific Reports)
Abstract The aim of the present study was to evaluate the effectiveness of a Cannonau pomace extract loaded in nutriosomes in intestinal oxidative stress and a subacute model of Parkinson disease and compare the results with those previously obtained with a Nasco pomace extract loaded in the same nutriosomes. In this study, Cannonau pomace was extracted using ultrasound-assisted maceration to obtain a polyphenol-rich extract. The extract at two different concentrations (5 and 10 mg/mL) was loaded in the same nutriosomes previously used to deliver Nasco pomace extract were loaded in nutriosomes. The main physico-chemical and technological characteristics of the obtained vesicles, along with their stability over time were measured. The in vitro biocompatibility and ability of nutriosomes to protect intestinal epithelial cells (Caco-2) from oxidative damages, were evaluated. Finally, the effectiveness of repeated administration of Cannonau extract in dispersion or loaded in nutriosomes against the neurotoxic effects in mice was evaluated. The resulting vesicles had uniform distribution, controlled the release of payloads, were biocompatible, like nutriosomes loading Nasco pomace extract, protected the intestinal cells against damages induced by hydrogen peroxide, in a better extent than the Nasco nutriosomes. However, no significant neuroprotective effects were observed in in vivo experiments performed using a subacute model of Parkinson disease, unlike previous results obtained with Nasco pomace extract loaded nutriosomes. This discrepancy is possibly due to the absence of key polyphenols like procyanidin B2 in the Cannonau extract, which are instead present in the Nasco extract. The findings suggest that while nutriosomes enhance the bioavailability and efficacy of grape pomace extracts in vitro, their therapeutic potential in vivo may depend on the specific phenolic profile of the extract used. Further research is needed to optimize formulations and explore synergistic combinations for improved neuroprotective outcomes.